2021
DOI: 10.1142/s0217751x21501463
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino mass, leptogenesis and sterile neutrino dark matter in inverse seesaw framework

Abstract: We study [Formula: see text] flavor symmetric inverse seesaw model which has the possibility of simultaneously addressing neutrino phenomenology, dark matter (DM) and baryon asymmetry of the universe (BAU) through leptogenesis. The model is the extension of the standard model by the addition of two (RH) neutrinos and three sterile fermions leading to a keV scale sterile neutrino DM and two pairs of quasi-Dirac states. The CP violating decay of the lightest quasi-Dirac pair present in the model generates lepton… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Recently, it has also been shown that BAU can be successfully generated in a S 4 discrete symmetric framework with TM 1 mixing [235] taking lepton flavor effects into consideration. For a few more recent studies on various discrete flavor symmetry and leptogenesis see [142,[236][237][238][239][240][241].…”
Section: B Flavor Symmetry and Baryon Asymmetry Of The Universe (Bau)mentioning
confidence: 99%
“…Recently, it has also been shown that BAU can be successfully generated in a S 4 discrete symmetric framework with TM 1 mixing [235] taking lepton flavor effects into consideration. For a few more recent studies on various discrete flavor symmetry and leptogenesis see [142,[236][237][238][239][240][241].…”
Section: B Flavor Symmetry and Baryon Asymmetry Of The Universe (Bau)mentioning
confidence: 99%